2005
DOI: 10.1016/j.bbrc.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent binding of calmodulin to neuronal gap junction proteins

Abstract: We examined the interactions of calmodulin with neuronal gap junction proteins connexin35 (Cx35) from perch, its mouse homologue Cx36, and the related perch Cx34.7 using surface plasmon resonance. Calmodulin bound to the C-terminal domains of all three connexins with rapid kinetics in a concentration- and Ca2+-dependent manner. Dissociation was also very rapid. K(d)'s for calmodulin binding at a high-affinity site ranged from 11 to 72 nM, and K(1/2)'s for Ca2+ were between 3 and 5 microM. No binding to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 35 publications
6
64
0
Order By: Relevance
“…Subsequent autophosphorylation at T(286), which enables the kinase to interact with further targets and/or substrate proteins (14,15,23), may then facilitate the binding of CTB to its corresponding substrate recognition motif at the catalytic segment of the kinase. Of note, the carboxyl-terminal binding site of Cx36 overlaps entirely with a sequence identified as a CaM binding site (24). This fact offers a further argument for a subsequential processing of both Cx36 segments during interaction with the kinase.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent autophosphorylation at T(286), which enables the kinase to interact with further targets and/or substrate proteins (14,15,23), may then facilitate the binding of CTB to its corresponding substrate recognition motif at the catalytic segment of the kinase. Of note, the carboxyl-terminal binding site of Cx36 overlaps entirely with a sequence identified as a CaM binding site (24). This fact offers a further argument for a subsequential processing of both Cx36 segments during interaction with the kinase.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the Ca 2ϩ spike generated in the axon terminal of an Mb1-BC may depolarize the membrane potential of its neighboring Mb1-BCs large enough to trigger the Ca 2ϩ spike. It has been reported that gap junctions can be modulated by intracellular Ca 2ϩ (Burr et al, 2005;Alev et al, 2008). However, the Ca 2ϩ channels are localized to the axon terminal of Mb1-BCs (Tachibana et al, 1993), and thus the gap junctions located at the distal dendrites may have a merit that they are not easily modulated by Ca 2ϩ diffused from the axon terminal.…”
Section: Discussionmentioning
confidence: 98%
“…The cytoplasmic domains of Cx36 involved in the alkalotic mechanism of pH have also been implicated in channel trafficking and other forms of gating. Indeed, the four most C-terminal amino acids are directly implicated in the binding of the zonula occludens-1 scaffolding protein (33) and more proximally, a calmodulin binding site was mapped to residues 273-291 (34). Furthermore, the protein kinase A-mediated phosphorylation of Cx36 that induces uncoupling occurs at S293 and S110 of the CTand CL-domains (25).…”
Section: Discussionmentioning
confidence: 99%